Simulating the impact of geographic targeting on poverty alleviation in Morocco : what are the gains from disaggregation ? - Douidich, Mohammed (Policy research working paper, 2008)
"The authors employ the recently completed "poverty map" for Morocco, referring to the year 2004, as a tool for an ex-ante evaluation of the distributional incidence of geographic targeting of public resources. They simulate the impact on poverty of transferring an exogenously given budget to geographically defined sub-groups of the population according to their relative poverty status. In both rural and urban areas, the findings reveal large gains from targeting smaller administrative units, such as communes or districts. However, these gains are still far from the poverty reduction that would be possible had the planners had access to information on household level income or consumption. The results indicate that a useful way forward might be to combine fine geographic targeting using a poverty map with within-community targeting mechanisms. "--World Bank web site